Comparative and contrastive observations on scientific titles written in English and Spanish - Soler, Marta Viviana (2011)
This research focuses on the structural construction of scientific titles in English and Spanish in research papers (RP) and review papers (RVP) in the biological and social sciences. The questions raised were (i) whether structural construction is a key distinctive feature between RP and RVP titles; (ii) whether the inherent peculiarities of scientific disciplines imprint differences on the structural constructions of RP and RVP titles; and (iii) whether language-specific differences can be identified. To this end, a total of 1140 titles were analyzed, words per title were counted to measure their length and all structural constructions detected were registered. The major findings are: (a) the prevalence of nominal-group titles as a linguistic strategy of scientific discourse rather than as a disciplinary, generic or language characteristic; (b) the frequency of full-sentence construction in RP titles of the biological sciences; (c) the predominance of RP compound titles in the social sciences, and more flexibility of Spanish in the use of punctuation marks for the division of this title type; and (d) statistically significant differences in the length of RP titles in terms of discipline and language. Lines of evidence from this research contribute to underlining suggestions on how to guide novice scientists to write titles appropriately.